RESPON MORPHOLOGI TANAMAN SEDAP MALAM (Polianthes tuberose L. cv. Roro Anteng) TERHADAP PEMBERIAN COLCHICINE - Ainun Zuhrah; Nurul Aini; Tatik Wardiyati (Universitas Tribhuwana Tunggadewi, 2010)
Sedap malam (Polianthes tuberose L) is cut flower, broadcast flower and natural oil crop. The aims of this research is to increased quality and productivity of flowers. Field experiment was conducted during Februari to September 2008 in polibag and Factorial Randomized Block Design was applied with three (3) replications. The treatment consist of 4 level of colchicines concentration (0, 100, 200 and 300 ppm) and 3 level length of inundation (3, 6 and 9 hour). The result showed that there is an interaction between concentration and length of inundation on length of flower stalk, size of flower and time of harvest. Application of 100 ppm and 3 hour inundation made longer stalk of flower but become shorter when continue inundation up to 9 hour. Size of flower increased with increased concentration and inundation, but colchicine did not affected number of flowers